A GIS-RANCOM integrated methodology for post-disaster debris waste storage site selection problem - Uzun, M. F.; Bilisik, O. N.; Baracli, H. (SPRINGER, 2026)
In the context of disaster management systems, effective waste management processes represent a critical component in terms of environmental sustainability, public health, occupational health, and safety. The objective of the present study is to ascertain the most suitable locations for the provisional storage of debris waste that will be generated following a severe and destructive earthquake for the city of Istanbul, which is highly susceptible to seismic activity, to minimize the financial costs of waste management and the harmful effects of waste. This study integrates geographic information systems (GIS) with the RANking Comparison Method (RANCOM), a multi-criteria decision-making (MCDM) method. The most suitable candidate sites for temporary storage areas (TSAs) for debris waste were determined based on criteria established in accordance with expert opinions, literature studies, and guidelines prepared by international organizations such as the United Nations (UN), the United States Federal Emergency Management Agency (FEMA), and the Environmental Protection Agency (EPA). 15 potential TSAs were identified for the entire Istanbul Province based on expert opinions regarding the specified criteria. In the accuracy assessment of the GIS-based maps obtained, the overall accuracy was calculated as 92%, with a kappa value of 0.94. It is assumed that the developed hybrid methodology can be applied to all other disaster scenarios.
Keywords: Disaster waste management; Temporary storage sites; Earthquake waste; Debris waste; The expected Istanbul earthquake; Multi criteria decision method; 2016 KUMAMOTO EARTHQUAKE; DISASTER WASTE; MANAGEMENT; OPTIMIZATION; Environmental Sciences & Ecology